Rheological properties of SS316l MIM feedstock prepared with different particle sizes and powder loadings - Sri Yulis, M. Amin; Khairur Rijal, Jamaludin; Norhamidi, Muhamad, Assoc. Prof. Dr. (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/